Mothers' knowledge of mother-to-child transmission of HIV and infant feeding practices in Juba, South Sudan - Lily Lejeng; Rose Opiyo Okoyo; Joyce Olenja (Health and Social Sciences Research Institute - South Sudan (HSSRI-SS), 2020)
Introduction: While exclusive breastfeeding for the first six months of life is recommended for HIV-infected mothers, this may not be practiced fully in South Sudan; exclusive formula feeding, which is the best alternative to breastfeeding, may not be practical. Objective: To assess the knowledge of mother-to-child transmission of HIV (MTCT) and practices of feeding infants in the first six months of life among HIV-infected mothers attending Antiretroviral Therapy Centres in Juba Teaching Hospital (JTH) and Juba Military Hospital (JMH). Method: A cross-sectional study in which 304 HIV-infected mothers with children aged 6-18 months were interviewed between October and December 2016 using structured questionnaires. Key informant interviews (KIIs) and focus group discussions (FGDs) were also conducted using interview guides. Quantitative data was analysed using Statistics Package for Social Sciences software. Chi-square test was used to test the presence of significant association between the variables and the association is statistically significant when the p-value is < 0.05. Multiple logistic regression analysis was used to identify which predictor variables have major effect on the dependent variable. Qualitative data was transcribed in English and summarized according to the key themes, and the information obtained was used to supplement and interpret the findings of the quantitative data. Results: Only 120 (40%) of the HIV-infected mothers had a good knowledge of MTCT; 213 mothers (70.1%) practiced mixed feeding, 70 (23.0%) practiced exclusive breastfeeding and 20 (6.6%) practiced exclusive formula feeding. The factors that were found to have a positive effect on choice of infant feeding methods were having more than one child (odds ratio = 0.303, 95% Confidence interval: 0.161-0.571, p = 0.001) and participation in the prevention of mother-to-child transmission of HIV programme (PMTCT) (odds ratio = 2.260, 95% Confidence interval: 1.251-4.084, p = 0.007). Stigma (p = 0.248) and mothers' knowledge of MTCT (p = 0.072) were not statistically significantly associated with the mothers' infant feeding practices. Conclusion: Knowledge of MTCT is low. Mixed feeding before six months of age is predominant among the HIV-infected mothers. It is therefore recommended that HIV-infected mothers receive adequate information from counsellors regarding MTCT and exclusive breastfeeding for the first six months of an infant's life.